Implications of Vitamin D Deficiency in Chronic Kidney Disease - A Systematic Review - Paola Cristina Ceratto; Maiara Vanusa Guedes Ribeiro; Renata Calciolari Rossi e Silva; Debora Tavares de Resende e Silva (Archives of Clinical Nephrology - Peertechz Publications, 2016)
Vitamin D presents interesting pleiotropic effects for the CKD patient (effect and anti-inflammatory properties). Patients with chronic kidney disease (CKD) have impaired endothelial function and the Vitamin D and its analogs may play a role in regulation of endothelial function and inflammation. Therefore, it is increasingly observed that CKD is characterized by a state of chronic inflammation that appears to be linked to oxidative stress, endothelial dysfunction and vascular calcification. Previous studies have shown that vitamin D administration in chronic renal failure patients produces therapeutic effects suggesting an inverse relationship between the presence of 25-hydroxyvitamin D [25 (OH) D] and inflammatory biomarkers. It is emphasized so the importance of proper maintenance of the vitamin D status, since it plays an important role in the management of inflammation and immunity, contributing to the reduction of morbidity and mortality in patients with CKD. In addition there is cumulative evidence showing the low level of vitamin D associations with the development and progression of chronic kidney disease, cardiovascular complications and high mortality.